Germ Cell - RG, Ahmed (IntechOpen, 2018)
This book focuses on the development and biology of germ cell and is edited by Ahmed RG, associate professor and Doctor of Developmental and Experimental Biology, Division of Anatomy and Embryology, Zoology Department, Faculty of Science, Beni-Suef University, Egypt. While many articles have appeared in journals on germ cell, this book provides you with a rare treat - an extensive and intensive study on it. It is one of a kind, offering important and valuable information about the biology of germ cell. This book covers the specification, regulation, and reprogramming of germ cell and germ line stem cells. This book provides important information about the new insight into germ cell signaling and the genotoxic in vitro studies in testicular germ cells. This book offers significant results about the origin, specification, and development of the female germ line in placental mammals and the germ cell tumors and their association with pregnancy.